Les premiers colons de l’ancienne Haïti et leurs attaches en métropole, à l’aube des premiers établissements (1650-1700) - Philippe Hroděj (Les Cahiers de Framespa)
When the first long-lasting settlements appeared in what was to become Saint-Domingue, the settlers were only a handful. Their isolation was reinforced by the geographical relief which separated the different settlement areas, by the remoteness of the Lesser Antilles, by commercial links which long remained irregular, and by unceasing wars due to the belated implementation of treatises and anticipation of conflicts. The astonishing death rate during the first year was an additional factor: the climate was hostile and gained control. In these conditions, the people who lived there had to invent new landmarks and to become closer to the other European nations. In short, French, English, and Spanish people knew each other and perfectly knew the Dutch merchants who were often the only ones able to provide supplies. Maintaining a link thus had value only for those who survived in a still new environment. This population was heterogeneous: from the indentured servant (enlisted to cultivate tobacco or to hunt) to the officer, from the deserter to the settler, to the missionaries, buccaneers, pirates, or privateers, so many originally different lives finally met in America. The ability to move over long distances was extraordinary, and dealing with the Atlantic without evoking the Indian Ocean and the South Sea makes no sense. Those liquid zones were so familiar that they became natural extensions. What remains is the attachment to the motherland maintained by family ties. Become looser, probably overshadowed in public archives, these ties persisted. The need for money, the necessity for the colonist to have someone trustful to manage his business on the other side of the ocean was compensated by the interest of knowing someone in America to send a youngest son to. And there was always, or at least often (even if this became fainter as time passed), the plan of returning home after making a fortune.